TRANSFORMASI DAKWAH DIGITAL SANTRI MELAUI PELATIHAN DI PESANTREN MAHASISWA AL-HIKAM MALANG - Hazin, Mufarrihul; Turhan Yani, Muhammad; Zawawi, Ahmad Abdullah; Rahmawati, Nur Wedia Devi (Batara Wisnu : Indonesian Journal of Community Services, 2025)
This research aims to improve the digital da’wah skills of students at the Al-Hikam Malang Student Islamic Boarding School through the Participatory Action Research (PAR) method. With the rapid development of digital technology, Islamic boarding schools need to adapt their da’wah methods to utilize social media and digital platforms effectively. The research began with the identification of problems using digital questionnaires, which revealed three main skills required: the essence of digital da’wah, the creation of da’wah content, and the use of editing applications. Based on these findings, the training was designed and implemented involving 42 students. The training material includes the essence of digital da’wah, the urgency and concept of creating da’wah content, as well as the use of editing applications and hands-on practice. The pre-test showed a moderate average score of 3.2, indicating a basic understanding but skills that need to be developed. Post-test after training showed a significant improvement with an average score of 4.5, indicating progress in digital da’wah skills and understanding. The results of the study show that the training has succeeded in improving the skills of students in utilizing digital technology for da’wah and affirms the importance of a structured and interactive approach in similar training programs in the future